Implementation of Decision Number 56/Pdt.G/2019/Pn Stb in Cases of Construction of Buildings on Land Loans - Tasya Umayya Hasibuan; Elvira Dewi Ginting (Universitas Islam Malang, 2023)
Decision Number 56/Pdt.G/2019/Pn Stb There was a case in Paya Perupuk Village, Tanjung Pura District which involved the problem of constructing buildings on land belonging to other people where according to the agreement that had been described and signed together that the plot of land was loaned to meet the needs life. In this study using empirical juridical research with field research methods (field research) associated with library research methods (library research) as an effort to interpret the law. The approaches used in this research are statutory and factual approaches. The results of the first study, the Panel of Judges considered that the Defendants did not have a valid basis or strong basis for building a house and occupying the land object of the case and at trial there was no relevant and valid and authentic evidence on which the Defendants built a house and occupied the land object of the case the. So according to the Panel of Judges, it can be concluded that the Plaintiff is the legal owner of the land object of the case. Second, implementation of Supreme Court decision No. 56/Pdt.G/2019/PN Stb in the case of building construction on borrowed land in Paya Prupuk Village, Tanjung Pura District, based on information provided by the community, it is known that the case of refusing to return the borrowed land was a big mistake made by landlord to the landlord. The first reason was because he had violated the agreement that had been agreed upon, the second was taking rights that did not belong to him so that his actions had harmed the owner, and did not implement the judge's decision No. 56/Pdt.G/2019/PN.Stb. Keywords: Land Disputes; Paya Perupuk Village; Absentee Land